Keistimewaan Bahasa Arab Dan Tantangan Pengajarannya - Muhammad Rizal Zaenulloh; Ujang Syahid; Neng Nurul Hidayanti (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Each language has its own specialties and characteristics, including Arabic which has its own specialties and characteristics that are not found in other languages, including derivation of words, i'rab, wide range of places where sound comes out, the existence of fa'il which is directly attached to fi'il and breadth of vocabulary. Even though Arabic has many advantages, in reality it is a challenge for teachers in teaching it, including the many nahwu rules, the existence of i'rab, fontetic problems, limited contemporary dictionaries and lack of ability to use them as well as the many different meanings of words. different. Therefore, this research aims to find solutions to overcome these teaching challenges. The method used in this research is a qualitative method with descriptive analysis which aims to determine the existence of the features of the Arabic language and the challenges of teaching it according to modern linguists. The results of this research, to face these challenges, Arabic language teachers should be able to simplify and update the teaching of rules by choosing material that is more important for students, asking students to get used to using dictionaries, and increasing listening and speaking training.